Hoppy birthday, Jo-Jo! - Goodhart, Pippa; Birkett, Georgie (New York : Crabtree Pub., 2005)
Jo-Jo wishes she were small like her new baby sister Roo until Dad says Jo-Jo is big enough to have a birthday party with invited guests, jumping games, and hidden presents.
Resource Links.
1.4
K-3
Keywords: Babies -- Fiction; Birthdays -- Fiction; Growth -- Fiction; Kangaroos -- Fiction; Parties -- Fiction; Birthdays -- Fiction; Growth -- Fiction; Infants -- Fiction; Kangaroos -- Fiction; Parties -- Fiction